Anti-inflammatory labdane diterpenoids from the aerial parts of Leonurus japonicus. (June 2023) - Wei, Quan-Hao; Cao, Xin-Xin; Xu, De-Feng; Wang, Shu-Ting; Zhang, Jun-Sheng; Zhang, Hua
Abstract: Twenty-two labdane-type diterpenoids, including ten pairs of 15-epimers and a pair of 13, 15-epimers, were obtained from the aerial parts of a well-known medicinal plant Leonurus japonicus Houtt. While these epimers were separated by chiral HPLC, their structures were established mainly via spectroscopic methods especially NMR, X-ray crystallography and ECD techniques. Among them, seventeen compounds, encompassing three pairs of solvolysis artefacts likely due to the use of ethanol as extracting solvent, were reported for the first time in the current work. Our preliminary anti-inflammatory screening demonstrated that seven diterpenoids displayed noteworthy inhibitory effect on the NO production in LPS-induced RAW264.7 cells. In addition, the release of pro-inflammatory factors TNF-α, IL-1β and IL-6, as well as the expression of iNOS and COX-2 proteins, was also suppressed by the unreported 15, 16-epoxy-6β-hydroxy-15α-methoxy-7, 16-dioxolabd-8, 13-diene. Further investigation into the preliminary anti-inflammatory mechanism of this compound indicated that it could block the activation of NF-κB signaling pathway. Graphical abstract: Twenty-two labdane-type diterpenoids including 17 previously unreported ones were obtained from Leonurus japonicus, with selective ones showing noteworthy anti-inflammatory effects. Image 1 Highlights: Seventeen unreported labdane-type diterpenoids were obtained from Leonurus japonicus. The structures were elucidated by analyses of spectroscopic data and X-ray crystallography. Selective compounds showed noteworthy inhibitory effect on the NO production. Compound 1 could block the activation of NF-κB signaling pathway.